2016
DOI: 10.1016/j.physletb.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive dijet production in deep inelastic scattering and photon-hadron collisions in the color glass condensate

Abstract: We study exclusive dijet production in coherent diffractive processes in deep inelastic scattering and real (and virtual) photon-hadron (γ ( * ) -h) collisions in the Color Glass Condensate formalism at leading order. We show that the diffractive dijet cross section is sensitive to the color-dipole orientation in the transverse plane, and is a good probe of possible correlations between the qqdipole transverse separation vector r and the dipole impact parameter b. We also investigate the diffractive dijet azim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 120 publications
3
70
1
Order By: Relevance
“…When applied to inclusive hadron, jet, vector meson and D meson production, this approach results in good agreement with LHC data[53][54][55][56][57] 4. The differential dΠ is defined as (2π) 2 |P |d|P ||∆|d|∆|dy 1 dy 2 .…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…When applied to inclusive hadron, jet, vector meson and D meson production, this approach results in good agreement with LHC data[53][54][55][56][57] 4. The differential dΠ is defined as (2π) 2 |P |d|P ||∆|d|∆|dy 1 dy 2 .…”
mentioning
confidence: 64%
“…While coherent diffractive dijet production allows to access the target's spatial geometry [4][5][6][7][8], inclusive and incoherent diffractive dijet cross sections are sensitive to multi-gluon correlations in the target [9,10] (see also [11][12][13][14][15]). In the near back-to-back correlation limit, where the mean dijet momentum is much larger than the recoil momentum, the inclusive dijet production cross section can be expressed in terms of the Weizsäcker-Williams transverse momentum dependent gluon distributions (TMDs), allowing experimental access to these fundamental quantities [9,[16][17][18][19].…”
mentioning
confidence: 99%
“…The comparison between our theory predictions with previous E791 experiment demonstrates the importance of the soft factor contributions. In the following, we will present numeric results for cross sections measurable at a future EIC, focusing on coherent diffractive dijet production in e + p collisions [10,11,15].…”
mentioning
confidence: 99%
“…In the framework of high-energy QCD, diffractive dijet production in photon-proton and photon-nucleus collisions was considered in the Color Glass Condensate (CGC) formalism at leading order in ref. [69]. It was found that the effects of gluon saturation can be searched for in the dijet azimuthal angle correlations and t distributions.…”
Section: Discussionmentioning
confidence: 99%